2019
DOI: 10.18632/aging.102260
|View full text |Cite
|
Sign up to set email alerts
|

Genomic deletion of TLR2 induces aggravated white matter damage and deteriorated neurobehavioral functions in mouse models of Alzheimer’s disease

Abstract: Toll-like receptor-2 (TLR2), a member of the TLR family, plays an important role in the initiation and regulation of immune/inflammation response, which is a critical mechanism underlying Alzheimer’s disease (AD). To clarify the role of TLR2 in the pathological process of AD, in the present study, TLR2 knockout plus APPswe/PSEN1dE9 transgenic mice (AD-TLR2KO) were generated. Neurobehavioral tests and brain MRI scan were conducted on mice at the age of 12 months. Additionally, neuron loss was evaluated using Ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 58 publications
3
32
0
Order By: Relevance
“…Similar results were obtained for TLR2 expression, except at the basal state of SMC subjects [ 165 , 166 ]. This is in line with data which found that the genomic deletion of TLR2 markedly deteriorated the neurobehavioral functions in a mouse model of AD [ 167 ]. This suggests that a functional balance should exist between the hyper- and hypoactivation of the TLRs [ 167 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similar results were obtained for TLR2 expression, except at the basal state of SMC subjects [ 165 , 166 ]. This is in line with data which found that the genomic deletion of TLR2 markedly deteriorated the neurobehavioral functions in a mouse model of AD [ 167 ]. This suggests that a functional balance should exist between the hyper- and hypoactivation of the TLRs [ 167 ].…”
Section: Discussionsupporting
confidence: 91%
“…This is in line with data which found that the genomic deletion of TLR2 markedly deteriorated the neurobehavioral functions in a mouse model of AD [ 167 ]. This suggests that a functional balance should exist between the hyper- and hypoactivation of the TLRs [ 167 ]. Conversely this decrease may also contribute further during infection to the deposition of Aβ by the decreased TLR2 expression [ 144 ].…”
Section: Discussionsupporting
confidence: 91%
“…TLR2 binds to Aβ and mediates the Aβ phagocytosis by microglia [ 207 ]. Dysregulation of the TLR2 pathway accelerated memory impairment in AD mice, either through inhibition [ 208 , 209 , 210 ] or activation [ 207 ]. None of these agents have reached clinical trials for AD therapy.…”
Section: Novel Therapeutic Approachmentioning
confidence: 99%
“…The importance of TLR signaling in preventing the development of AD is highlighted by studies demonstrating how activation of TLR 2, 4, and 9 signaling can reduce brain pathology and plaque build-up (Tahara et al, 2006 ). Furthermore, TLR 4 and 2 knock-out mice demonstrate increased amyloid plaque burden and cognitive decline (Song et al, 2011 ; Zhou et al, 2019 ). The above affects appear to occur via reduced microglial phagocytosis of amyloid plaques.…”
Section: Pip Effects On Microglial Functions and Implications For Neurodegenerationmentioning
confidence: 99%